(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
This paper draws upon a close textual reading of Kierkegaard’s Upbuilding Discourses and parts of The Sickness Unto Death. It argues that his characterization of the ’immediate person’ is a fitting description for impatient patients, in an impatient world. His thoughts on patience provide a clear and grounding message for trainees cutting their teeth in an environment that screams the opposite.